Performance of constructed wetland technology in removal of conventional pollutants from wastewater contaminated with ibuprofen - Teo, Malcolm Eng Hui. (2013)
Constructed Wetland (CW) technology has been proven to be very useful for the removal of conventional pollutant in, such as Chemical Oxygen Demands (COD), Ammonium (NH4+), and Total Phosphate (TP) from various kinds of wastewaters, and has been an up and rising topic in recent times. However, a rising concern in the treatment of wastewater using constructed wetlands is the occurrence of pharmaceutical product, which are regarded as emerging pollutants in wastewater treatment, posing potential threats to water environment, human health and also possibly bringing adverse effects on the performance of CWs due to its bioremediation characteristic.